EFEKTIVITAS RESTORATIVE JUSTICE DALAM PENYELESAIAN KASUS KRIMINALITAS RINGAN: STUDI KASUS DENGAN METODE STUDI KOMPARATIF - Idris, Maulana Fahmi; Kriswandaru, Althea Serafim; Pratiwi, Berliant (MAGISTRA Law Review, 2025)
Restorative justice has gained attention as an alternative approach to resolving minor criminal cases, offering a rehabilitative and community-oriented process. In Indonesia, its implementation aims to reduce the judicial burden and promote offender reintegration. However, inconsistencies in application and its effectiveness in reducing recidivism remain concerns. This study evaluates the effectiveness of restorative justice in Indonesia by examining case resolution speed, victim satisfaction, and recidivism rates. Using a comparative study method with qualitative and quantitative approaches, data were collected from legal documents, case studies (2018–2023), and stakeholder interviews. The findings show that cases resolved through restorative justice increased from 500 in 2018 to 2,300 in 2023, reflecting broader adoption. Survey results indicate 70% of victims were satisfied with restorative justice outcomes, compared to 50% in conventional proceedings. The recidivism rate for offenders undergoing restorative justice was 40%, lower than 55% in conventional sentencing but still higher than the Netherlands (65%) and Canada (68%). This study highlights the importance of law enforcement support, victim participation, and community involvement in the success of restorative justice. Strengthening national policies is essential to ensure more consistent and effective implementation. These findings offer valuable insights for policymakers in enhancing restorative justice practices in Indonesia to build a more efficient and rehabilitative criminal justice system.